Entrepreneurial Ecosystems and Economic Development Policy. Issue 1 (February 2023) - Qian, Haifeng; Acs, Zoltan J.
The authors discuss economic development policy facing the burgeoning entrepreneurial ecosystem research. They aim to answer four questions. First, how are entrepreneurial ecosystems different from regional innovation systems and clusters, two related frameworks that had been vastly popular among economic development policy makers prior to the rise of entrepreneurial ecosystems? Second, what are the key findings in the entrepreneurial ecosystem research that can guide economic development policy making? Third, how should economic development policy be adjusted under the entrepreneurial ecosystem approach? Finally, what does the ongoing debate on the geographical boundaries of entrepreneurial ecosystems mean for economic development policy?